2013
DOI: 10.4103/0255-0857.115625
|View full text |Cite
|
Sign up to set email alerts
|

Use of GenoType® MTBDRplus assay to assess drug resistance and mutation patterns of multidrug-resistant tuberculosis isolates in northern India

Abstract: The GenoType® MTBDRplus assay is highly sensitive with short turnaround times and a rapid test for the detection of the most common mutations conferring resistance in MDR-TB strains that can readily be included in a routine laboratory workflow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 25 publications
7
8
0
Order By: Relevance
“…The most common katG, inhA, and ahpC promoter mutations in our study were identified at frequencies similar to those reported previously (11,23,24). However, our finding of 315ACC mutations among INH s specimens (2.8%) was unexpected.…”
Section: Discussionsupporting
confidence: 89%
“…The most common katG, inhA, and ahpC promoter mutations in our study were identified at frequencies similar to those reported previously (11,23,24). However, our finding of 315ACC mutations among INH s specimens (2.8%) was unexpected.…”
Section: Discussionsupporting
confidence: 89%
“…Twenty-four (96%) of the 25 isolates, which were determined to be rifampicin-resistant with the BACTEC 460 TB method, were found to be rifampicin-resistant with GenoType MTBDRplus. Our result was similar to other reports from India, France, Germany and Ethiopia (16, [23][24][25]. One isolate (4%) was susceptible to rifampicin.…”
Section: Discussionsupporting
confidence: 92%
“…In 2018, in the study by Kamiri et al, among the 35 specimens identified as RIF-resistant using the Geno-TypeMTBDRplus assay, 23 (65%) carried the S531L, eight isolates (22%) showed mutation in codon H526Y and four isolates (11%) in D516V codon (32). In 2013, in the study by Maurya et al, the frequency of rpoB mutation was 28 in S531L (62.3%), eight in D516V (17.7%), six in H526Y (11.1%), one in the H526D (2.2%) region and nine (20%) unknown mutations (absence of one or more wild-type) among a total of 45 MDR-TB strains (23). In 2017, in the study by Abanda et al, among the 48 isolates determined as RIF-resistant using the GenoTypeMTBDRplus assay, 41 (85%) had the S531L mutation and three isolates (6%) showed mutation in codon H526Y.…”
Section: Discussionmentioning
confidence: 95%
“…Further studies are required to fully characterize the molecular epidemiology of these isolates in Uganda, especially studies employing high throughput sequencing approaches to uncover all the potential resistance conferring mutations. Since the commercial rapid molecular assays for TB target only high confidence mutations to swiftly detect resistance to anti-TB drugs [ 31 , 32 , 42 , 50 ], absence of targets is troublesome as it makes it nearly impossible to employ rapid molecular assays to detect certain resistant strains in clinical samples. On the other hand, strains that lacked mutations could harbour resistance conferring mutations in other genes e.g.…”
Section: Discussionmentioning
confidence: 99%